What do learners perceive? A sociolinguistic survey on Iranian English language learners’ attitudes on mainstream ELT versus critical ELT - Davari, Hossein (Journal of Modern Languages, 2016)
The growing presence of English especially through English language teaching (ELT) is going to considerably influence any language education policy and planning worldwide. Alongside such an influence, the appearance of critical voices in the field of applied linguistics has resulted in some controversial discussions around English and ELT. While this topic has received considerable attention, reviewing the literature on the topic shows that the survey of learners’ attitudes, as one of the most important stakeholders in any language-in-education planning, has been mostly neglected. In this paper, the author attempts to investigate the Iranian English language learners’ attitudes towards English and ELT to study their trends. To gain insight into the issue, a mixed-methods approach, including both qualitative and quantitative methods, was designed and conducted. In the first phase, both focus group and one-to-one interviews were conducted. The content analysis along with the rich literature on the topic yielded a twelve-item Likert-scale questionnaire. To survey the learners’ attitudes at large, a questionnaire survey was conducted on 548 participants. Presenting and discussing the findings under four categories reveal that Iranian learners mostly tend to the mainstream trend and lack of awareness and sensitivity towards possible influences of English and ELT on their language and culture is tangible.